ESBL Genotypes in Fluoroquinolone-Resistant and Fluoroquinolone-Susceptible ESBL-Producing Escherichia coli Urinary Isolates in Manitoba - Philippe RS Lagacé-Wiens; Kim A Nichol; Lindsay E Nicolle; Mel R DeCorby; Melissa McCracken; Michelle J Alfa; Michael R Mulvey; George G Zhanel (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: Extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli are increasingly common in nosocomial and community settings. Furthermore, fluoroquinolone (FQ) and even multidrug resistance (MDR) appear to be associated with certain ESBL genotypes. The purpose of the present study was to determine which ESBL genotypes are associated with FQ and MDR in E coli urinary isolates in Manitoba.